PRODUKSI KEDELAI DENA 1 (Glycine max (L) Merrill.) DI BAWAH TEGAKAN KELAPA SAWIT - Kamsia Dorliana Sitanggang (UNIVERSITAS LABUHANBATU, 2019)
The objectives of this research is to know the production of Dena-1 varieties under and without oil palm tree (TM 8) using peat soil media in polybags. The results showed that there were differences in the production of Dena 1 soybean varieties planted under palm and open areas using peat soil media, where soybeans planted under oil palm (TM8) were unable to produce only reach vegetative growth, while soybeans were planted in the open yields average number of pods of 5-6 plant pods, average number of seeds of 10 crop seeds and average seed weight of 1.31 grams of planting. Keywords: crop, peat, soybean